(untitled) (Revista de Estudos da Linguagem, 1992)
ln this paper I discuss some research results on syntactic variation and change which took place in OId Portuguese. Based on texts from the 14th and 15th centuries I discuss: (a) the variation involving ser/estar and the diffusion of estar to atributive structures (both locative and descriptive); (b) the variation between singular and plural as weIl as the loss ofagreement marks in the Past Participle in those structures where in conjunction with haver or ter it could be reinterpreted as a compound tense; and (c) fmaIly, I present evidence to show that in some syntactic and semantic contextsnumber agreement involving a verb and its subject was a variable phenomenon in Old Portuguese.